Atelierhaus Bonn 1992-2000. - Granoux, Pierre; Leineweber, Norvin; Atelierhaus, Bonn (Bonn : [s.n.], 2000)
Barros, Renata ; Brandt, Renate ; Von Chappius, Hildegard ; Cheng, Wang ; Diané, Aboubacar ; Duniko ; Edorh, Sokey ; Gertz, Rita ; Gibbs ; Granoux, Pierre ; Haifeng, Rita ; Lei, Zhang ; Leineweber, Norvin ; Muhandi, Chain ; Parekh, Manisha ; Pavlova, Valentina ; Read, Marcos Lora ; Schmitt, Angelika ; Schöck, Dieter ; Stammer, Karl-Theo ; Tayou, Pascale-Marthine ; Terk ; Udechukwu, Obiora ; Umezulike, Dilompri ; Verbeek, Jan ; Zeuch, Jan
Atelierhaus Bonn, 1992-2000, overzicht tentoonstellingen
kunstcatalogus